2022
DOI: 10.52711/2231-5659.2022.00013
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review on Toxicity and Pharmacological Aspects of Foeniculum vulgare with Emphasis on Anti-Cancer Potential

Abstract: The recent advancements in field of genomics and synthetic biology has paved the way for determination and utilization of pharmaceutical properties of beneficial plants. Foeniculum vulgare is a member of Apiaceae family, commonly known as fennel. It is globally distributed aromatic medicinal herb. F. vulgare falls in the category of World’s most important medicinal herb because of its economic status and pharmaceutical industrial applications. It has been used as herbal treatment for a longer period of time as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent studies have highlighted on the beneficial effects of medicinal plants used in poultry feeding, the physiological evaluation of medicinal plants in the poultry industry showed a strong effect as a substitute for natural growth stimulants, improved egg components and reduced fat content while increasing alpha-Linolenic acid and n-3 fatty acid content (2, 23 and 25). Foeniculum vulgare Mill is a well-known medicinal plant that has been used by humans since ancient times because of its distinctive flavor, it is known worldwide as Fennel, recent developments in the field of genomics and synthetic biology have paved the way for the use of the medicinal properties of this plant, as pharmacological experiments have shown that the Fennel has strong therapeutic effects due to its pharmacological properties that are very important for human health (4). As for the poultry industry, the Fennel when it was included as a feed additive to the diet of laying hens showed significant effects on the external and internal quality characteristics of eggs (31).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted on the beneficial effects of medicinal plants used in poultry feeding, the physiological evaluation of medicinal plants in the poultry industry showed a strong effect as a substitute for natural growth stimulants, improved egg components and reduced fat content while increasing alpha-Linolenic acid and n-3 fatty acid content (2, 23 and 25). Foeniculum vulgare Mill is a well-known medicinal plant that has been used by humans since ancient times because of its distinctive flavor, it is known worldwide as Fennel, recent developments in the field of genomics and synthetic biology have paved the way for the use of the medicinal properties of this plant, as pharmacological experiments have shown that the Fennel has strong therapeutic effects due to its pharmacological properties that are very important for human health (4). As for the poultry industry, the Fennel when it was included as a feed additive to the diet of laying hens showed significant effects on the external and internal quality characteristics of eggs (31).…”
Section: Introductionmentioning
confidence: 99%